Inhibition of soluble epoxide hydrolase alleviated atherosclerosis by reducing monocyte infiltration in Ldlr−/− mice. (September 2016) - Li, Dan; Liu, Yajin; Zhang, Xu; Lv, Huizhen; Pang, Wei; Sun, Xiaoli; Gan, Li-Ming; Hammock, Bruce D.; Ai, Ding; Zhu, Yi
Abstract: Rationale: Circulating monocytes play pivotal roles in chronic inflammatory diseases. Epoxyeicosatrienoic acids (EETs), metabolites of arachidonic acid, are known to have anti-inflammatory effects and are hydrolyzed by soluble epoxide hydrolase (sEH). Objective: We aimed to investigate the effect of sEH inhibition in atherogenesis. Methods and results: Mice with low-density lipoprotein receptor deficiency ( Ldlr −/− ) with or without sEH inhibitor, and Ldlr/sEH double-knockout (DK) mice were fed a Western-type diet (WTD) for 6 weeks to induce arteriosclerosis. Both sEH inhibition and gene depletion decreased the WTD–induced hyperlipidemia, plaque area and macrophage infiltration in mice arterial wall. Ly6C hi infiltration of monocytes remained similar in blood, spleen and bone marrow of DK mice, but was decreased in aortic lesions. To further assess the role of sEH or EETs in monocyte/macrophage infiltration in atherogenesis, we transplanted DK bone marrow into Ldlr −/− recipients, and then fed mice the WTD. Aortic lesions and Ly6C hi monocyte infiltration were reduced in mice with transplanted bone marrow of DK mice without diminishing the cholesterol level. Furthermore, sEH inhibition or gene depletion increased the ratio of EETs/DHETs and diminished the expression of P-selectin glycoprotein ligand 1 (PSGL-1) in mice peripheral-blood mononuclear cells. Monocyte adhesion to P-selectin and to tumor necrosis factor α–activated endothelial cells was also diminished by sEH inhibition. Conclusion: sEH inhibition and gene depletion attenuated atherosclerosis in mice by decreasing the infiltration of monocytes into the artery wall. EET and PSGL-1 may play pivotal roles in monocyte/macrophage infiltration and atherogenesis. Highlights: The inhibition of and knockout sEH ameliorated the lesion of atherosclerosis in Ldlr -/- mice. The mechanism of monocyte with sEH deficiency in adhesion to aortic lesion is proposed. The inhibition of sEH increased the ratio of EETs/DHETs and diminished the expression of P-selectin glycoprotein ligand 1 in monocyte from the mice.